IMPLEMENTASI EKSTRAKURIKULER KRGIATAN KEAGAMAAN DALAM PROGRAM KEPUTRIAN DI SMKN 5 MALANG - Intan Sahara; Nur Hasan; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The women's program is carried out to realize Islamic young women who are expected to make students understand more about things related to women, both physically and spiritually. It aims to improve the quality of young women as the nation's hope. In its implementation, of course, good planning is needed before the implementation of the program, besides that it can also organize the implementation of the women's program properly. these two things are the basis for achieving the goals of the program. The results of the implementation of the women's program will have very good impacts not only on students but also on the environment at school and in the community.